Personality, Identity Styles, and Fundamentalism During Emerging Adulthood. Issue 3 (2nd July 2016) - Bartoszuk, Karin; Deal, James E.
ABSTRACT: This study examined the associations among personality, identity style, and fundamentalism. The initial sample included 808 students from 2 state universities (in the upper Midwest and Southeast United States). Of those students, 440 students self-identified as Protestant and were included. Testing mediation effects of identity styles on the relationship between personality and fundamentalism revealed only moderate direct effects between personality and fundamentalism, but 4 distinct patterns of indirect effects supporting the process-oriented model proposed by Duriez and colleagues. Results are discussed in terms of similarities and differences with other studies, with implications for future research outlined.